Propuesta de intervención urbana en el mirador de Santa Elena de la parroquia rural San Bartolomé de Pinllo - Aguilar Salazar, Andrea Isabel (2025)
San Bartolomé de Pinllo is a rural parish in the canton of Ambato, which is characterized by its spatial delimitation and heritage elements. The cultural and intangible heritage, including local legends and gastronomy, are outstanding tourist attractions in the area. It has a network of streams and ditches, the steep terrain limits its growth, however, it offers panoramic views of the city of Ambato. This work focuses on making a proposal for urban intervention in the Santa Elena viewpoint, which is experiencing deterioration, disuse and accessibility and identity challenges, so a comprehensive urban design is proposed to revitalize the Santa Elena viewpoint in order to enhance its tourist attraction, preserve its natural environment and improve infrastructure and services. The execution of the project is based on an applied modality methodology, the paradigm assumed in the research is qualitative with a non-probabilistic approach, with convenience sampling. This resulted in the relevance of the Santa Elena viewpoint for the city, the need for the recovery of public space and the applicable urban intervention strategies. In this sense, an urban intervention proposal is developed based on the conceptualization that it is an urban viewpoint, with the characteristic that it is located in a natural site. This foundation is used so that the architectural design is integrated with the surrounding landscape. Likewise, urban strategies are proposed that strengthen the identity and accessibility of public space, in order to enhance its tourist attraction.